2012
DOI: 10.1007/s12311-011-0349-z
|View full text |Cite
|
Sign up to set email alerts
|

Ruptured Intrameatal Aneurysm of the Anterior Inferior Cerebellar Artery Accompanying an Arteriovenous Malformation: a Case Report

Abstract: The distal anterior inferior cerebellar artery (AICA) aneurysms located inside the internal auditory canal are rare. The association of the distal AICA aneurysms and an arteriovenous malformation (AVM) on the same arterial trunk is exceptional. Eight reports of a total of ten cases have been published and all of the reported aneurysms were located in the meatal or postmeatal segment of the AICA. Herein, we report a case of ruptured aneurysm in the intrameatal portion of the AICA accompanying an AVM fed by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…A possible explanation for this deficit may be nerve manipulation during surgery or internal auditory artery injury 9) . During the operation, we found that the aneurysm was tightly adhered to the nerves as described in other reports 6 9 10) . Therefore, during the dissection the eighth nerve was manipulated.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…A possible explanation for this deficit may be nerve manipulation during surgery or internal auditory artery injury 9) . During the operation, we found that the aneurysm was tightly adhered to the nerves as described in other reports 6 9 10) . Therefore, during the dissection the eighth nerve was manipulated.…”
Section: Discussionsupporting
confidence: 78%
“…As for treatment, microsurgical direct clipping is considered to be the first line of treatment 6 10) . Endovascular treatment is not considered as the primary treatment because of difficulty in catheter navigation and the possibility of parent artery occlusion, but is used for elderly patients and those in poor general condition 7) .…”
Section: Discussionmentioning
confidence: 99%
“…[10] To the best of our knowledge, intrameatal AICA aneurysm has been reported in only 26 patients (21 women), including our patient. [3,5,6,8,9,11,13,14,15,[17][18][19][20]22,25,29,32,33,35,37,38,40,41] e patients' ages ranged from 35 to 83 years, with a mean age of 61.3 ± 14.0 (standard deviation) and median age of 62 years. e comorbidities included hypertension in seven patients, dyslipidemia in four patients, and diabetes mellitus in three patients.…”
Section: Discussionmentioning
confidence: 99%
“…[4,10,26,29] However, an aneurysm in the internal auditory canal (IAC) is rare; only 25 cases have been reported thus far. [3,5,6,8,9,11,13,14,15,[17][18][19][20]22,25,29,32,33,35,37,38,40,41] It generally presents with subarachnoid hemorrhage (SAH). Herein, we have reported an extremely rare case of intrameatal aneurysm caused by dissection of the AICA, presenting initially with the eighth nerve palsy and then the seventh nerve palsy without SAH.…”
Section: Introductionmentioning
confidence: 99%
“…circulation seem to contribute to the development of distal AICA aneurysms, 61,62 as well as high-flow situations, as vascularized tumors, 62,63 arteriovenous fistula, 64 and malformations. 65,66 Also, a case of ruptured aneurysm of a SAA feeding a dural arteriovenous fistula was reported. 64 Isolated AICA aneurysms have been interpreted in two major groups: pontine (proximal, premeatal) and cerebellar (distal, postmeatal) 67,68 ; parent vessel occlusion may lead to life-threatening consequences in the former group 68 ; therefore, these patients are candidates to arterial bypass.…”
Section: Discussionmentioning
confidence: 99%